Antineutrophil cytoplasmic autoantibodies in uveitis - "Vodjgani M; Baghbani HN; Hajati J " (Acta Medica Iranica, 2000)
Antineutrophil cytoplasmic autoantibodies were detected in patients with some autoimmune and vascular disease such as Wegner’s granulomatosis polyarthritis nodosa and systemic lupus erythematosus. Indirect immunofluorescence technique was employed to detect these autoantibodies. By this method, two general patterns of antineutrophil cytoplasmic autoantibodies were seen: a cytoplasmic (C-ANCA) and a perinuclear form (P-ANCA). These antibodies also were observed in uveitis. In this study the presence of antineutrophil cytoplasmic autoantibodies in 25 patients with uveitis and its relationship with uveitis and its relationship with anatomical location of the disease is evaluated. According to the results antineutrophil cytoplasmic autoantibodies was detected in 16% (4 out of 25) of the patients all of them being C-ANCA type. The results also showed that there was not any significant correlation between the presence of antineutrophil cytoplasmic autoantibodies and anatomical location of the disease (P=0.65).